Dr. Nneoma Wamkpah — Deep Plane Facelift — Palo Alto - Wamkpah, Nneoma (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Nneoma Wamkpah, practicing in Palo Alto, USA. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-002977; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; usa; palo alto